PENERAPAN GAYA KEPEMIMPINAN DEMOKRATIS KEPALA DESA PULE KECAMATAN PULE KABUPATEN TRENGGALEK - Setyowati, Herlina; Khotimah, Chusnul; F, Zidan Bariqli; C, Anang Sugeng (Gapenas Publisher, 2023)
Leadership style is a leader's efforts to influence others. The democratic style is very popular used by a leader in the modernization era. The characteristics of the leadership style are related to the opinions of both parties between the leader and his subordinates, a goal of a leader who is able to absorb opinions, and input from various parties in a decision. The facts from this research were obtained through the Head of Pule Village, Pule District, Trenggalek Regency. From this study it can be concluded that they are still not successful in carrying out their leadership. Where the employees are still free and as they wish in doing the work without any direct orders from superiors. The work carried out by employees that should be done according to the set time, is still often late for work, in terms of attendance even employees at the Pule Village Office, Pule District, Trenggalek Regency are still often late, leaving the office during working hours, even returning home before time determined by the regulations in the village hall